Obelia geniculata - Moura, Carlos J. (Zenodo, 2015)
Obelia geniculata (fig. 4I) Sertularia geniculata Linnaeus, 1758: 812. Obelia geniculata .— Hincks, 1868: 149, pl. 25 figs 1,1a.— Patriti, 1970: 35, figs 44, 44bis.— Cornelius, 1975a: 272, figs 1a–d, 5a–c.— Cornelius, 1982: 119 –120.—Cornelius, 1990: 550–557.— Vervoort, 1993: 558 –559.— Cornelius, 1995b: 301 –303, fig. 70.— Medel & López-González, 1996: 206.— Medel & Vervoort, 2000: 54 –58.—Peña Cantero & García Carrascosa, 2002: 162–163, fig. 31d.— Govindarajan et al., 2005: 213 –222, fig. 1. Laomedea geniculata .— Da Cunha, 1944: 61, fig. 35. Material studied . Ormonde, stn 4 : fertile colonies, very abundant on the brown alga Laminaria ochroleuca Bachelot de la Pylaie; DBUA 1524.01. Remarks . Oceana (2005) reported an Obelia species, possibly corresponding to O. geniculata. The present manuscript confirms this species presence at the top of the Ormonde seamount. Reported distribution . Eastern Atlantic.—Widespread, from Iceland (Broch 1918) to South Africa (Millard 1975). Mediterranean.—Widespread (e.g. García Corrales et al. 1978; Peña Cantero & García Carrascosa 2002). Elsewhere.—Historically considered a cosmopolitan species (e.g. Picard 1958a; Millard 1975), but Govindarajan et al . (2005) found considerable genetic differentiation, indicative of cryptic speciation, between specimens from the North Atlantic, Japan and New Zealand. O. geniculata was originally described from Dover, UK (Linnaeus 1758; Cornelius 1975a) being thus probable that the Gorringe specimens are correctly identified. Published as part of Moura, Carlos J., 2015, The hydrozoan fauna (Cnidaria: Hydrozoa) from the peaks of the Ormonde and Gettysburg seamounts (Gorringe Bank, NE Atlantic), pp. 148-180 in Zootaxa 3972 (2) on pages 166-167, DOI:10.11646/zootaxa.3972.2.2, http://zenodo.org/record/237108